Preparation process of marine concrete structure surface anti-erosion cement-based material

CN122254858BActive Publication Date: 2026-10-27WEIHAI HIGHWAY DEV CENT +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610477885.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-13
Publication Date
2026-10-27
Estimated Expiration
2046-04-13

AI Technical Summary

Technical Problem

硫酸盐与水泥水化产物反应后生成钙矾石等膨胀性产物,引起混凝土内部产生膨胀应力,导致结构的强度丧失和破坏

Benefits of technology

本发明先采用氢氧化钡对煅烧后的水滑石进行处理,利用氢氧化钙提供的氢氧根离子对水滑石的层间结构进行重建的同时,使钡离子也进入到层间形成Ba2+@LDHs。进一步地,本发明以叙永石粉、硝酸钙、硅酸钠为原料进行反应,从而在叙永石的纳米管腔中形成水化硅酸钙C-S-H,进一步煅烧后失水转变为活性硅酸钙,从而得到本发明的改性叙永石粉。将采用上述的Ba2+@LDHs、改性叙永石粉与磷酸镁水泥等形成的改性磷酸镁水泥制备防侵蚀水泥基材料时,其在混凝土结构表面形成的防护层不仅具有良好的粘结能力,可以减少防护层脱落造成的结构防护失效,而且还能够同时提升对氯离子和硫酸根离子的抗侵蚀能力。这是由于:一方面所述磷酸镁水泥水化后形成的胶凝产物鸟粪石具有优异的粘结能力,能够牢固地结合在混凝土结构表面,同时所述乳化沥青不仅能够提升防护层的粘结能力,还能够提高防护层的抗渗性能,从而减少氯离子、硫酸根离子的侵蚀。另一方面,所述Ba2+@LDHs能够在磷酸镁水泥水化期间将剩余的磷酸盐吸附存储在层间,其中的一部分与钡离子形成硫酸钡沉淀,从而实现对磷酸盐的固化,不仅可以防止磷酸盐过滤导致残留在防护层中,服役期间遇水溶解后造成防护层孔隙率升高,抗侵蚀能力下降的问题,而且在遇到硫酸根离子侵蚀后,所述Ba2+@LDHs可使硫酸根进入其层间与磷酸根交换,将硫酸根固定在层间,减少其扩散进入混凝土结构中,而且被交换释放出的所述磷酸根与伴随着硫酸根同步侵入的氯离子进入改性叙永石的纳米管腔中,并与其中的活性硅酸钙遇水后水化释放的钙离子共同反应形成氯磷灰石,这种物质难溶于水且化学性质稳定,从而将氯离子固化在叙永石的纳米管腔中,同时,所述活性硅酸钙水化后形成的水化硅酸钙凝胶还有助于封闭所述纳米管腔,进一步起到固化其中氯离子和硫酸根离子,减少扩散的作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122254858B_ABST
    Figure CN122254858B_ABST
Patent Text Reader

Abstract

The application discloses a preparation process of a marine concrete structure surface anti-erosion cement-based material, and comprises the following steps: (1) putting calcined hydrotalcite powder into a barium hydroxide hot solution for dipping treatment to obtain Ba 2+ @LDHs powder. (2) uniformly mixing serpentine powder, calcium nitrate and water, heating and keeping warm, then continuously keeping warm and aging under stirring after dropwise adding a sodium silicate solution, then separating a solid product, calcining the solid product, grinding the calcined product to obtain modified serpentine powder. 2+ (3) mixing magnesium phosphate cement, Ba @LDHs, modified serpentine powder and a retarder powder, and grinding to obtain modified magnesium phosphate cement powder. (4) uniformly mixing the modified magnesium phosphate cement powder, emulsified asphalt, inorganic fillers and fibers with water. The cement-based material has good bonding capacity with the concrete structure, reduces structure protection failure caused by falling, and simultaneously improves the anti-erosion capacity to chloride ions and sulfate ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete material preparation technology, specifically to a preparation process for an anti-corrosion cement-based material for the surface of marine concrete structures. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] Concrete, as an economical, practical, and high-performance building material, is widely used in projects ranging from cross-sea bridges and port terminals to offshore oil platforms and subsea tunnels. However, the unique harshness of the marine environment poses a persistent and severe threat to concrete structures. The interplay of factors such as chloride ion corrosion, sulfate corrosion, wave impact, and the attachment and growth of marine organisms in seawater makes the durability of marine engineering concrete structures a major challenge that the engineering construction field must address. Chloride ion corrosion is widely recognized as the primary factor leading to the deterioration of reinforced concrete structures.

[0004] Chloride ions can penetrate the protective layer of concrete to reach the surface of reinforcing steel, damaging the passivation film and triggering electrochemical corrosion. Once corrosion begins, the expansion of the steel generates significant internal stress on the surrounding concrete, leading to cracking and spalling, further accelerating the penetration of corrosive media and creating a vicious cycle. This process is particularly severe in tidal and splash zones, where alternating wet and dry conditions greatly promote chloride ion transport and accumulation. Besides chloride ion corrosion, sulfate ions in seawater also have a significant corrosive effect on concrete. Sulfates react with cement hydration products to form expansive products such as ettringite, causing internal expansion stress in the concrete, leading to structural strength loss and failure. Therefore, improving the corrosion resistance of marine concrete structures is a crucial measure to extend their safe service life. Summary of the Invention

[0005] This invention provides a process for preparing a cement-based material for corrosion protection of marine concrete structures. This cement-based material not only has good adhesion to concrete structures, helping to reduce structural protection failures caused by detachment, but also simultaneously improves resistance to chloride and sulfate ions. Specifically, the technical solution of this invention is as follows.

[0006] A process for preparing an anti-corrosion cement-based material for the surface of marine concrete structures includes the following steps: (1) The calcined hydrotalcite powder was immersed in a hot barium hydroxide solution for treatment. After the treatment, the solid product was separated and dried to obtain Ba. 2+@LDHs powder, for future reference.

[0007] (2) After mixing Xuyong stone powder, calcium nitrate and water, heat and keep warm. Then, add sodium silicate solution dropwise under stirring. After completion, continue to keep warm and age. Then, separate the solid product and calcine it. After cooling to room temperature, grind the calcined product to obtain modified Xuyong stone powder for later use.

[0008] (3) Add magnesium phosphate cement and the Ba 2+ @LDHs, the modified Xuyong stone powder, and the retarder powder are mixed and ground to obtain modified magnesium phosphate cement powder for later use.

[0009] (4) Using the modified magnesium phosphate cement powder, emulsified asphalt, inorganic filler and fiber as raw materials, mix them evenly and then add mixing water and stir evenly to obtain the anti-corrosion cement-based material.

[0010] Further, in step (1), the calcination temperature of the hydrotalcite powder is 410~480℃, and the calcination time is 35~50min. Optionally, the fineness of the hydrotalcite powder is 200~400 mesh.

[0011] Further, in step (1), the mass ratio of the hydrotalcite powder to the barium hydroxide hot solution is 1:25~30. Optionally, the concentration of the barium hydroxide hot solution is 13~17 wt.%.

[0012] Furthermore, in step (1), the immersion treatment time is 1.5 to 2 hours.

[0013] Further, in step (2), the ratio of the Xuyong stone powder, calcium nitrate and water is 1g:0.09~0.14g:20~30mL, and the Ca / Si ratio of the sodium silicate to the calcium nitrate is 0.8~1.5.

[0014] Further, in step (2), the heating and heat preservation temperature is 60~70℃. Optionally, the aging time is 24~32 hours.

[0015] Furthermore, in step (2), the calcination treatment is carried out at a temperature of 600~750℃ for a time of 40~65min.

[0016] Furthermore, in step (2), the fineness of the modified Xuyong stone powder is 200~350 mesh.

[0017] Further, in step (3), the magnesium phosphate cement and Ba 2+ The ratio of LDHs, modified Xuyong stone powder, and retarder is 105~120 parts by weight: 21~26 parts by weight: 15~18 parts by weight: 5.5~7 parts by weight.

[0018] Furthermore, in step (3), the retarder includes at least one of boric acid, borax, etc.

[0019] Furthermore, in step (3), the fineness of the modified magnesium phosphate cement powder is 300~400 mesh.

[0020] Further, in step (4), the ratio of modified magnesium phosphate cement powder, emulsified asphalt, inorganic filler, and fiber is 100 parts by weight: 10~15 parts by weight: 4.5~6 parts by weight: 3~5 parts by weight. The mass ratio of mixing water to modified magnesium phosphate cement powder is 0.38~0.43:1.

[0021] Furthermore, in step (4), the solid content of the emulsified asphalt is 40~50 wt.%.

[0022] Further, in step (4), the inorganic filler includes at least one of the following: fly ash, silica fume, calcium carbonate, quartz powder, glass powder, etc. Optionally, the fineness of the inorganic filler is 500~700 mesh.

[0023] Further, in step (4), the fiber includes at least one of polyethylene fiber, polypropylene fiber, polyvinyl alcohol fiber, and polyacrylonitrile fiber. Optionally, the fiber has a length of 5-20 mm and a diameter of 0.1-0.15 mm.

[0024] Compared with the prior art, the present invention has at least the following beneficial technical effects: This invention first treats calcined hydrotalcite with barium hydroxide. While utilizing the hydroxide ions provided by calcium hydroxide to rebuild the interlayer structure of the hydrotalcite, barium ions also enter the interlayer to form Ba. 2+ @LDHs. Further, this invention uses pyrite powder, calcium nitrate, and sodium silicate as raw materials to react and form hydrated calcium silicate (CSH) within the nanotubes of pyrite. After further calcination, it loses water and transforms into active calcium silicate, thus obtaining the modified pyrite powder of this invention. The above-mentioned Ba... 2+ When modified magnesium phosphate cement, formed by LDHs, modified Xuyong stone powder, and magnesium phosphate cement, is used to prepare anti-corrosion cement-based materials, the protective layer it forms on the surface of concrete structures not only has good adhesion, reducing structural protection failure caused by protective layer detachment, but also simultaneously improves the resistance to chloride and sulfate ions. This is because: on the one hand, the struvite formed after the hydration of the magnesium phosphate cement has excellent adhesion, firmly bonding to the surface of the concrete structure; on the other hand, the emulsified asphalt not only improves the adhesion of the protective layer but also enhances its impermeability, thereby reducing the erosion of chloride and sulfate ions. On the other hand, the Ba... 2+@LDHs can adsorb and store residual phosphates in the interlayer during the hydration of magnesium phosphate cement. A portion of these phosphates reacts with barium ions to form barium sulfate precipitate, thus solidifying the phosphates. This not only prevents phosphate residues from remaining in the protective layer after filtration and dissolving in water during service, thus increasing the porosity and reducing corrosion resistance of the protective layer, but also prevents the formation of barium sulfate precipitates after encountering sulfate ion attack. 2+ @LDHs allow sulfate ions to enter the interlayer and exchange with phosphate ions, fixing the sulfate ions in the interlayer and reducing their diffusion into the concrete structure. Furthermore, the phosphate ions released during the exchange, along with chloride ions that simultaneously invade the modified pyrite nanotubes, react with the calcium ions released from the hydration of the active calcium silicate to form chlorapatite. This substance is poorly soluble in water and chemically stable, thus solidifying chloride ions within the pyrite nanotubes. Simultaneously, the hydrated calcium silicate gel formed after the active calcium silicate hydrates further helps to seal the nanotubes, further solidifying the chloride and sulfate ions and reducing their diffusion. Attached Figure Description

[0025] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Hereinafter, embodiments of the invention will be described in detail with reference to the accompanying drawings, wherein: Figure 1 The image shows a sample of modified magnesium phosphate cement powder from Example 1 below.

[0026] Figure 2 The image shows a sample of the modified magnesium phosphate cement powder from Example 2 below.

[0027] Figure 3 The image shows a sample of the modified magnesium phosphate cement powder from Example 3 below.

[0028] Figure 4 The image shows a sample of the modified magnesium phosphate cement powder from Example 4 below.

[0029] Figure 5 The image shows a sample of the modified magnesium phosphate cement powder from Example 5 below. Detailed Implementation

[0030] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. The present invention will now be further described in conjunction with the accompanying drawings and specific embodiments.

[0031] Example 1: A preparation process for an anti-corrosion cement-based material for the surface of marine concrete structures, comprising the following steps: (1) Magnesium aluminum hydrotalcite (Mg6A) with a fineness of 200 mesh l2 (CO3)(OH) 16 Calcium hydrotalcite powder was obtained by heating 4H₂O at a heating rate of 10℃ / min to 450℃ and holding for 40 min, then cooling to room temperature. This powder was mixed with a 15 wt.% barium hydroxide hot solution at 80℃ in a mass ratio of 1:30. The resulting mixture was then impregnated at 80℃ for 2 hours. After impregnation, the solid product was filtered out and dried at 100℃ to remove moisture, yielding Ba. 2+ @LDHs powder, for future reference.

[0032] (2) Mix Xuyong stone powder, calcium nitrate, and water at a ratio of 1g:0.11g:25mL and stir until homogeneous to form a mixture. Then heat to 65℃ and keep warm. Add sodium silicate solution dropwise to the mixture under stirring, according to a Ca / Si ratio of 0.12 between sodium silicate and calcium nitrate. After completion, continue to keep warm and age for 24 hours. Then filter out the solid product, dry it, and calcine it at a heating rate of 10℃ / min to 700℃ for 60min. After cooling to room temperature, grind the calcined product and pass it through a 300-mesh sieve to obtain modified Xuyong stone powder for later use.

[0033] (3) Add magnesium phosphate cement and Ba in this embodiment 2+ @LDHs, the modified Xuyong stone powder and borax of this embodiment are mixed in a ratio of 110 parts by weight: 23 parts by weight: 17 parts by weight: 6.2 parts by weight, then ground and passed through a 350-mesh sieve to obtain modified magnesium phosphate cement powder (e.g. Figure 1 (As shown), for later use.

[0034] (4) Take the following raw materials in the following proportions: 100 parts by weight of modified magnesium phosphate cement powder, 13 parts by weight of emulsified asphalt, 5 parts by weight of inorganic filler, and 4.5 parts by weight of fiber. Wherein: the solid content of the emulsified asphalt is 48 wt.%, the fiber is polyethylene fiber with a length of 10 mm and a diameter of 0.12 mm, and the inorganic filler is waste glass powder with a fineness of 600 mesh. Mix the above raw materials and stir for 3 minutes to obtain dry powder, then add 39 parts by weight of mixing water and stir for 2 minutes to obtain the anti-corrosion cement-based material.

[0035] Performance Testing: 1. The chloride ion diffusion coefficient of the anti-corrosion cementitious material in this embodiment was tested according to the "Standard for Test Methods of Long-Term Performance and Durability of Concrete" (GBT 50082-2024). 2. The anti-corrosion cementitious material of this embodiment was made into cylindrical specimens with a diameter of 50 mm and a height of 80 mm. These specimens were then immersed in a 5% sodium sulfate solution for 60 days. Afterward, the specimens were cut in half along their height and the SO4 content was tested. 2- The maximum diffusion depth was determined. The results are shown in the table below:

[0036] Example 2: A preparation process for an anti-corrosion cement-based material for the surface of marine concrete structures, comprising the following steps: (1) Magnesium aluminum hydrotalcite (Mg6A) with a fineness of 400 mesh l2 (CO3)(OH) 16 Calcium hydrotalcite powder was obtained by heating 4H₂O at a heating rate of 10℃ / min to 410℃ and holding for 50 min, then cooling to room temperature. This powder was mixed with a 13 wt.% barium hydroxide hot solution at 80℃ in a mass ratio of 1:30. The resulting mixture was then impregnated at 80℃ for 1.5 hours. After impregnation, the solid product was filtered out and dried at 100℃ to remove moisture, yielding Ba. 2+ @LDHs powder, for future reference.

[0037] (2) Mix Xuyong stone powder, calcium nitrate, and water at a ratio of 1g:0.09g:20mL and stir until homogeneous to form a mixture. Then heat to 60℃ and keep warm. Add sodium silicate solution dropwise to the mixture under stirring, according to a Ca / Si ratio of 0.8 between sodium silicate and calcium nitrate. After completion, continue to keep warm and age for 32 hours. Then filter out the solid product, dry it, and calcine it at a heating rate of 10℃ / min to 750℃ for 40min. After cooling to room temperature, grind the calcined product and pass it through a 200-mesh sieve to obtain modified Xuyong stone powder for later use.

[0038] (3) Add magnesium phosphate cement and Ba in this embodiment 2+ @LDHs, the modified Xuyong stone powder and borax of this embodiment are mixed in a ratio of 105 parts by weight: 21 parts by weight: 15 parts by weight: 5.5 parts by weight, then ground and passed through a 300-mesh sieve to obtain modified magnesium phosphate cement powder (e.g. Figure 2 (As shown), for later use.

[0039] (4) Take the following proportions of raw materials: 100 parts by weight of modified magnesium phosphate cement powder, 10 parts by weight of emulsified asphalt, 4.5 parts by weight of inorganic filler, and 3 parts by weight of fiber. Wherein: the solid content of the emulsified asphalt is 50 wt.%, the fiber is polypropylene fiber with a length of 5 mm and a diameter of 0.1 mm, and the inorganic filler is calcium carbonate with a fineness of 500 mesh. Mix the above raw materials and stir for 3 minutes to obtain dry powder. Then add 38 parts by weight of mixing water and stir for 2 minutes to obtain the anti-corrosion cement-based material.

[0040] Performance testing: The chloride ion diffusion coefficient and SO4 content of the corrosion-resistant cementitious material prepared in this embodiment were tested. 2- The maximum diffusion depth was determined using the same method as in Example 1 above, and the results are shown in the table below:

[0041] Example 3 A process for preparing an anti-corrosion cement-based material for the surface of marine concrete structures includes the following steps: (1) Magnesium aluminum hydrotalcite (Mg6A) with a fineness of 300 mesh l2 (CO3)(OH) 16 Calcium hydrotalcite powder was obtained by heating 4H₂O at a heating rate of 10℃ / min to 480℃ and holding for 35 min, followed by cooling to room temperature. This powder was then mixed with a 17wt.% barium hydroxide hot solution at 90℃ in a mass ratio of 1:25. The resulting mixture was then impregnated at 90℃ for 2 hours. After impregnation, the solid product was filtered out and dried at 100℃ to remove moisture, yielding Ba. 2+ @LDHs powder, for future reference.

[0042] (2) Mix Xuyong stone powder, calcium nitrate, and water at a ratio of 1g:0.14g:30mL and stir until homogeneous to form a mixture. Then heat to 70℃ and keep warm. Add sodium silicate solution dropwise to the mixture under stirring, according to a Ca / Si ratio of 1.5 between sodium silicate and calcium nitrate. After completion, continue to keep warm and age for 30 hours. Then filter out the solid product, dry it, and calcine it at a heating rate of 10℃ / min to 600℃ for 65min. After cooling to room temperature, grind the calcined product and pass it through a 350-mesh sieve to obtain modified Xuyong stone powder for later use.

[0043] (3) Add magnesium phosphate cement and Ba in this embodiment 2+ @LDHs, the modified Xuyong stone powder and boric acid powder of this embodiment are mixed in a ratio of 120 parts by weight: 26 parts by weight: 18 parts by weight: 7 parts by weight, then ground and passed through a 400-mesh sieve to obtain modified magnesium phosphate cement powder (e.g. Figure 3 (As shown), for later use.

[0044] (4) Take the following raw materials in the following proportions: 100 parts by weight of modified magnesium phosphate cement powder, 15 parts by weight of emulsified asphalt, 6 parts by weight of inorganic filler, and 5 parts by weight of fiber. Wherein: the solid content of the emulsified asphalt is 40 wt.%, the fiber is polyvinyl alcohol fiber with a length of 20 mm and a diameter of 0.15 mm, and the inorganic filler is silica fume with a fineness of 700 mesh. Mix the above raw materials and stir for 3 minutes to obtain dry powder, then add 43 parts by weight of mixing water and stir for 2 minutes to obtain the anti-corrosion cement-based material.

[0045] Performance testing: The chloride ion diffusion coefficient and SO4 content of the corrosion-resistant cementitious material prepared in this embodiment were tested. 2- The maximum diffusion depth was determined using the same method as in Example 1 above, and the results are shown in the table below:

[0046] Example 4 A process for preparing an anti-corrosion cement-based material for the surface of marine concrete structures includes the following steps: (1) Magnesium phosphate cement, modified Xuyong stone powder from Example 1 above, and borax were mixed in a ratio of 110 parts by weight: 17 parts by weight: 6.2 parts by weight, then ground and passed through a 350-mesh sieve to obtain modified magnesium phosphate cement powder (e.g. Figure 4 (As shown), for later use.

[0047] (2) Take the following raw materials in the following proportions: 100 parts by weight of modified magnesium phosphate cement powder, 13 parts by weight of emulsified asphalt, 5 parts by weight of inorganic filler, and 4.5 parts by weight of fiber. Wherein: the solid content of the emulsified asphalt is 48 wt.%, the fiber is polyethylene fiber with a length of 10 mm and a diameter of 0.12 mm, and the inorganic filler is waste glass powder with a fineness of 600 mesh. Mix the above raw materials and stir for 3 minutes to obtain dry powder, then add 39 parts by weight of mixing water and stir for 2 minutes to obtain the anti-corrosion cement-based material.

[0048] Performance testing: The chloride ion diffusion coefficient and SO4 content of the corrosion-resistant cementitious material prepared in this embodiment were tested. 2- The maximum diffusion depth was determined using the same method as in Example 1 above, and the results are shown in the table below:

[0049] Example 5 A process for preparing an anti-corrosion cement-based material for the surface of marine concrete structures includes the following steps: (1) Magnesium phosphate cement and Ba from Example 1 above are mixed together. 2+@LDHs and borax were mixed in a ratio of 110 parts by weight: 23 parts by weight: 6.2 parts by weight, then ground and passed through a 350-mesh sieve to obtain modified magnesium phosphate cement powder (e.g. Figure 5 (As shown), for later use.

[0050] (2) Take the following raw materials in the following proportions: 100 parts by weight of modified magnesium phosphate cement powder, 13 parts by weight of emulsified asphalt, 5 parts by weight of inorganic filler, and 4.5 parts by weight of fiber. Wherein: the solid content of the emulsified asphalt is 48 wt.%, the fiber is polyethylene fiber with a length of 10 mm and a diameter of 0.12 mm, and the inorganic filler is waste glass powder with a fineness of 600 mesh. Mix the above raw materials and stir for 3 minutes to obtain dry powder, then add 39 parts by weight of mixing water and stir for 2 minutes to obtain the anti-corrosion cement-based material.

[0051] Performance testing: The chloride ion diffusion coefficient and SO4 content of the corrosion-resistant cementitious material prepared in this embodiment were tested. 2- The maximum diffusion depth was determined using the same method as in Example 1 above, and the results are shown in the table below:

[0052] Example 6 A process for preparing an anti-corrosion cement-based material for the surface of marine concrete structures includes the following steps: (1) The Xuyong stone powder was heated to 600℃ at a heating rate of 10℃ / min and calcined for 65min. After cooling to room temperature, the calcined product was ground and passed through a 350-mesh sieve to obtain modified Xuyong stone powder for later use.

[0053] (2) Add magnesium phosphate cement and Ba from Example 1 above. 2+ @LDHs, the modified Xuyong stone powder and boric acid powder of this embodiment are mixed in a ratio of 120 parts by weight: 26 parts by weight: 18 parts by weight: 7 parts by weight, then ground and passed through a 400-mesh sieve to obtain modified magnesium phosphate cement powder for later use.

[0054] (3) Take the following raw materials in the following proportions: 100 parts by weight of modified magnesium phosphate cement powder, 15 parts by weight of emulsified asphalt, 6 parts by weight of inorganic filler, and 5 parts by weight of fiber. Wherein: the solid content of the emulsified asphalt is 40 wt.%, the fiber is polyvinyl alcohol fiber with a length of 20 mm and a diameter of 0.15 mm, and the inorganic filler is silica fume with a fineness of 700 mesh. Mix the above raw materials and stir for 3 minutes to obtain dry powder, then add 43 parts by weight of mixing water and stir for 2 minutes to obtain the anti-corrosion cement-based material.

[0055] Performance testing: The chloride ion diffusion coefficient and SO4 content of the corrosion-resistant cementitious material prepared in this embodiment were tested. 2-The maximum diffusion depth was determined using the same method as in Example 1 above, and the results are shown in the table below:

[0056] Example 7 A process for preparing an anti-corrosion cement-based material for the surface of marine concrete structures includes the following steps: (1) Magnesium aluminum hydrotalcite (Mg6A) with a fineness of 400 mesh l2 (CO3)(OH) 16 ·4H2O) is heated to 410℃ at a heating rate of 10℃ / min and held for 50min. After cooling to room temperature, calcined hydrotalcite powder is obtained and set aside for later use.

[0057] (2) The magnesium phosphate cement, the calcined hydrotalcite powder of this embodiment, the modified Xuyong stone powder of the above embodiment 2, and borax are mixed in a ratio of 105 parts by weight: 21 parts by weight: 15 parts by weight: 5.5 parts by weight and then ground. The mixture is then passed through a 300-mesh sieve to obtain modified magnesium phosphate cement powder for later use.

[0058] (3) Take the following proportions of raw materials: 100 parts by weight of modified magnesium phosphate cement powder, 10 parts by weight of emulsified asphalt, 4.5 parts by weight of inorganic filler, and 3 parts by weight of fiber. Wherein: the solid content of the emulsified asphalt is 50 wt.%, the fiber is polypropylene fiber with a length of 5 mm and a diameter of 0.1 mm, and the inorganic filler is calcium carbonate with a fineness of 500 mesh. Mix the above raw materials and stir for 3 minutes to obtain dry powder. Then add 38 parts by weight of mixing water and stir for 2 minutes to obtain the anti-corrosion cement-based material.

[0059] Performance testing: The chloride ion diffusion coefficient and SO4 content of the corrosion-resistant cementitious material prepared in this embodiment were tested. 2- The maximum diffusion depth was determined using the same method as in Example 1 above, and the results are shown in the table below:

[0060] Example 8 A process for preparing an anti-corrosion cement-based material for the surface of marine concrete structures includes the following steps: (1) Mix Xuyong stone powder, calcium nitrate, and water at a ratio of 1g:0.14g:30mL and stir until homogeneous to form a mixture. Then heat to 70℃ and keep warm. Add sodium silicate solution dropwise to the mixture under stirring, according to a Ca / Si ratio of 1.5 between sodium silicate and calcium nitrate. After completion, continue to keep warm and age for 30 hours. Then filter out the solid product, dry it, grind it, and pass it through a 350-mesh sieve to obtain modified Xuyong stone powder for later use.

[0061] (2) Add magnesium phosphate cement and Ba from Example 1 above.2+ @LDHs, the modified Xuyong stone powder and boric acid powder of this embodiment are mixed in a ratio of 120 parts by weight: 26 parts by weight: 18 parts by weight: 7 parts by weight, then ground and passed through a 400-mesh sieve to obtain modified magnesium phosphate cement powder for later use.

[0062] (3) Take the following raw materials in the following proportions: 100 parts by weight of modified magnesium phosphate cement powder, 15 parts by weight of emulsified asphalt, 6 parts by weight of inorganic filler, and 5 parts by weight of fiber. Wherein: the solid content of the emulsified asphalt is 40 wt.%, the fiber is polyvinyl alcohol fiber with a length of 20 mm and a diameter of 0.15 mm, and the inorganic filler is silica fume with a fineness of 700 mesh. Mix the above raw materials and stir for 3 minutes to obtain dry powder, then add 43 parts by weight of mixing water and stir for 2 minutes to obtain the anti-corrosion cement-based material.

[0063] Performance testing: The chloride ion diffusion coefficient and SO4 content of the corrosion-resistant cementitious material prepared in this embodiment were tested. 2- The maximum diffusion depth was determined using the same method as in Example 1 above, and the results are shown in the table below:

[0064] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A preparation process for an anti-corrosion cement-based material for the surface of marine concrete structures, characterized in that, Includes the following steps: (1) The calcined hydrotalcite powder was immersed in a hot barium hydroxide solution for treatment. After the treatment, the solid product was separated and dried to obtain Ba. 2+ @LDHs powder, for later use; (2) After mixing Xuyong stone powder, calcium nitrate and water, heat and keep warm. Then, add sodium silicate solution dropwise under stirring. After completion, continue to keep warm and age. Then, separate the solid product and calcine it. After cooling to room temperature, grind the calcined product to obtain modified Xuyong stone powder for later use. (3) Add magnesium phosphate cement and the Ba 2+ @LDHs, the modified Xuyong stone powder, and the retarder powder are mixed and ground to obtain modified magnesium phosphate cement powder for later use; (4) Using the modified magnesium phosphate cement powder, emulsified asphalt, inorganic filler and fiber as raw materials, mix them evenly and then add mixing water and stir evenly to obtain the anti-corrosion cement-based material.

2. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (1), the calcination temperature of the hydrotalcite powder is 410~480℃ and the time is 35~50min.

3. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (1), the fineness of the hydrotalcite powder is 200~400 mesh.

4. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (1), the mass ratio of the hydrotalcite powder to the barium hydroxide hot solution is 1:25~30.

5. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (1), the concentration of the barium hydroxide hot solution is 13~17 wt.%.

6. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (1), the immersion treatment time is 1.5 to 2 hours.

7. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (2), the ratio of Xuyong stone powder, calcium nitrate and water is 1g:0.09~0.14g:20~30mL, and the Ca / Si ratio of sodium silicate to calcium nitrate is 0.8~1.

5.

8. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (2), the heating and heat preservation temperature is 60~70℃.

9. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (2), the aging time is 24 to 32 hours.

10. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (2), the calcination treatment is carried out at a temperature of 600~750℃ for 40~65min.

11. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (2), the fineness of the modified Xuyong stone powder is 200~350 mesh.

12. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (3), the magnesium phosphate cement and Ba 2+ The ratio of LDHs, modified Xuyong stone powder, and retarder is 105~120 parts by weight: 21~26 parts by weight: 15~18 parts by weight: 5.5~7 parts by weight.

13. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (3), the retarder includes at least one of boric acid and borax.

14. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (3), the modified magnesium phosphate cement powder has a fineness of 300~400 mesh.

15. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to claim 1, characterized in that, In step (4), the ratio of modified magnesium phosphate cement powder, emulsified asphalt, inorganic filler, and fiber is 100 parts by weight: 10~15 parts by weight: 4.5~6 parts by weight: 3~5 parts by weight; the mass ratio of mixing water to modified magnesium phosphate cement powder is 0.38~0.43:

1.

16. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to any one of claims 1-15, characterized in that, In step (4), the solid content of the emulsified asphalt is 40~50 wt.%.

17. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to any one of claims 1-15, characterized in that, In step (4), the inorganic filler includes at least one of fly ash, silica fume, calcium carbonate, quartz powder, and glass powder.

18. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to any one of claims 1-15, characterized in that, In step (4), the fineness of the inorganic filler is 500~700 mesh.

19. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to any one of claims 1-15, characterized in that, In step (4), the fiber includes at least one of polyethylene fiber, polypropylene fiber, polyvinyl alcohol fiber, and polyacrylonitrile fiber.

20. The preparation process of the anti-corrosion cement-based material for marine concrete structures according to any one of claims 1-15, characterized in that, In step (4), the fiber has a length of 5~20mm and a diameter of 0.1~0.15mm.

Citation Information

Patent Citations

  • Concrete admixture and preparation method thereof

    CN112608069A

  • Modified hydrotalcite as well as preparation method and application thereof

    CN112777959A